Abnormal Gray Matter Shape, Thickness, and Volume in the Motor Cortico-Subcortical Loop in Idiopathic Rapid Eye Movement Sleep Behavior Disorder: Association with Clinical and Motor Features. (7th June 2017) - Rahayel, Shady; Postuma, Ronald B; Montplaisir, Jacques; Bedetti, Christophe; Brambati, Simona; Carrier, Julie; Monchi, Oury; Bourgouin, Pierre-Alexandre; Gaubert, Malo; Gagnon, Jean-François
Abstract: Idiopathic rapid eye movement sleep behavior disorder (iRBD) is a major risk factor for Parkinson's disease and dementia with Lewy bodies. Anatomical gray matter abnormalities in the motor cortico-subcortical loop areas remain under studied in iRBD patients. We acquired T1-weighted images and administrated quantitative motor tasks in 41 patients with polysomnography-confirmed iRBD and 41 healthy subjects. Cortical thickness and voxel-based morphometry (VBM) analyses were performed to investigate local cortical thickness and gray matter volume changes, vertex-based shape analysis to investigate shape of subcortical structures, and structure-based volumetric analyses to investigate volumes of subcortical and brainstem structures. Cortical thickness analysis revealed thinning in iRBD patients in bilateral medial superior frontal, orbitofrontal, anterior cingulate cortices, and the right dorsolateral primary motor cortex. VBM results showed lower gray matter volume in iRBD patients in the frontal lobes, anterior cingulate gyri, and caudate nucleus. Shape analysis revealed extensive surface contraction in the external and internal segments of the left pallidum. Clinical and motor impaired features in iRBD were associated with anomalies of the motor cortico-subcortical loop. In summary, iRBD patients showed numerous gray matter structural abnormalities in the motor cortico-subcortical loop, which are associated with lower motor performance and clinical manifestations of iRBD.